PENGARUH PENGETAHUAN TERHADAP KEPUTUSAN MENJADI NASABAH BANK SYARIAH MELALUI PEMEDIASI MINAT DAN KESADARAN - Erma Yuliani (Jurnal Ekonomi Manajemen dan Bisnis, 2021)
The condition of Islamic banking in Bali is very contradictory, seen from the Muslim population of 12.08 percent, but the number of Islamic bank customers is only 3 percent, it is interesting to explore the decision-making factors to become a customer of Islamic banks. This study aims to explain knowledge, interest, awareness, in constructing decisions. The population of this research is the customers of Bank Syariah Indonesia Kuta Bali Branch totaling 4,123 customers. The sample used is 112 respondents, respondents are customers of Bank Syariah Indonesia Kuta Bali Branch. This research was analyzed using SEM-PLS analysis technique. The results showed that knowledge did not have a positive and significant effect on interest, knowledge had a positive and significant effect on awareness, interest had a positive and significant effect on decisions, awareness had a positive and significant effect on decisions, had no significant effect on decisions, interest was proven to mediate the effect on decisions. decisions, awareness proved to be a partial mediator on the effect of knowledge on decisions. The theoretical implications of this research contribute to developing theoretical concepts related to factors of knowledge, interest, awareness in shaping decisions to become customers of Islamic banks. The practical implications provide insight to Islamic bank management that high knowledge in the community cannot make decisions, but with the role of interest and awareness as a mediator, knowledge can influence decisions.